The Oxford handbook of terrorism - Chenoweth, Erica 1980-; English, Richard 1963-; Gkophas, Andreas ca. 20./21. Jh; Kalybas, Stathēs N. 1964- (Oxford handbooks online, 2019)
This title systematically integrates the substantial body of scholarship on terrorism and counterterrorism before and after 9/11. In doing so, it introduces scholars and practitioners to state of the art approaches, methods, and issues in studying and teaching these vital phenomena. This handbook goes further than most existing collections by giving structure and direction to the fast-growing but somewhat disjointed field of terrorism studies. The volume locates terrorism within the wider spectrum of political violence instead of engaging in the widespread tendency towards treating terrorism as an exceptional act. Moreover, the volume makes a case for studying terrorism within its socio-historical context